ANALISIS MANAJEMEN ASET PADA SATUAN KERJA PEMERINTAH PUSAT DI KOTA PALU - Octanary, Doan (Katalogis, 2018)
The regulation No. 6, 2006 that rules the management of state/ local properties has changed the management of state assets. It is hoped that this rules can set a better asset structure and management. Fixed assets such as land and buildings are special concerns for the government. The value of land and building by 66% of total fix assets listed on LKPP 2015 illustrates their potentials. A well-managed assets is certainly necessary so that the assets can be organized effectively, efficiently, and provide added value. This study aims to determine the process of asset inventory, legal audit, asset valuation, asset optimization, as wel as the supervision and control of land and buildings in the central government units of Palu City. This is a qualitative research. Questionners distributed to 64 working units that manage land and buildingss. The result conclude that the inventory of assets, legal audit, asset valuation, also monitoring and control of land and buildings have been implemented very well. While the implementation of the asset optimization are at moderate level.